2019
DOI: 10.3390/ijerph16111875
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance and Development of Social Connection by People with Long-term Conditions: A Qualitative Study

Abstract: Social connection is important for people’s health and well-being. Social isolation arising from a lack of meaningful connection with others can result in deterioration of well-being with negative consequences for health. For people living with multiple long-term conditions, the building and maintaining of social connection may be challenging. The aim of this study was to explore with people with long-term conditions how they perceive they maintain and develop social connections. We undertook semi-structured i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
2
28
0
Order By: Relevance
“…Participants were enticed to use parks because of the opportunity to connect and to improve their health. Being connected with others is an important aspect of human health and wellbeing [ 45 , 46 ] that is, the two themes presented within “Enticing” are interlinked concepts. Previous studies have similarly shown that urban parks provide opportunities for people to connect with others in the natural environment [ 47 ], and people who spend time in a natural environment are more likely to report good health and wellbeing [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were enticed to use parks because of the opportunity to connect and to improve their health. Being connected with others is an important aspect of human health and wellbeing [ 45 , 46 ] that is, the two themes presented within “Enticing” are interlinked concepts. Previous studies have similarly shown that urban parks provide opportunities for people to connect with others in the natural environment [ 47 ], and people who spend time in a natural environment are more likely to report good health and wellbeing [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social connectedness, de ned as the practice of belonging and relatedness, is a vital determinant of human wellbeing. It is centred on quantitative and qualitative social assessments in interaction and relationship strength (1)(2)(3). Currently, in many parts of the world, the use of smart technology and social media is recognised as an enabler and facilitator of social connectedness (4-6).…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that social connectedness can be a powerful phenomenon to tap into when planning for public health interventions. Improved mental health, reduced depression, enhanced sense of belonging, improved health-seeking behaviour, reduced stress, enhanced self-esteem, and improved cognition are all notable bene ts of social connectedness (3,(8)(9)(10)(11)(12). Evidence has shown that people with decreased social connectedness have poor mental and physical health and higher morbidity and mortality compared to those with strong social connectedness (8)(9)(10)(11)13).…”
Section: Introductionmentioning
confidence: 99%
“…
Social connection via its elements of social coherence, integration, contribution, actualisation and acceptance is postulated to contribute both to the development of societal well-being (Keyes, 1998;Keyes & Shapiro, 2004) and individual well-being (Wilkinson et al, 2019).Social connection is instrumental in the development of societal well-being via bonding and bridging relationships (Putnam, 2000).Bonding relationships are those that form or strengthen bonds between individuals or groups with similar interests, situations, contexts or demographics. Bridging relationships are those that form or strengthen bridges between individuals or groups of dissimilar situations, interests or demographics.
…”
mentioning
confidence: 99%
“…Social connection via its elements of social coherence, integration, contribution, actualisation and acceptance is postulated to contribute both to the development of societal well-being (Keyes, 1998;Keyes & Shapiro, 2004) and individual well-being (Wilkinson et al, 2019).…”
mentioning
confidence: 99%